(untitled) (Journal of the College of Basic Education, 2026)
The current research seeks to identify the effect of the Learning to Mastery strategy on the achievement of Art Education Department students in the Elements of Art course. To achieve the objectives of the current research, the researcher adopted a quasi-experimental approach with two groups: an experimental group receiving instruction using the Learning to Mastery strategy, and a control group receiving instruction using the lecture method. Before beginning the experiment, a set of equivalence tests were conducted between the two groups. An achievement test was also constructed to measure the level of achievement in the Elements of Art course before and after implementation. After implementing the experiment, the research concluded the following: There is a clear effect of Learning to Mastery on the achievement of Art Education Department students in the Elements of Art course. There are statistically significant differences between the experimental and control groups, in favor of the experimental group.